PENGARUH MEDIA ICT DAN KECERDASAN LINGUISTIK TERHADAP HASIL BELAJAR BAHASA INGGRIS - Muslim Na; Fahri Yasin (Akademika, 2018)
This study aims to determine 1) The difference in English learning outcomes between training participants who are taught using ICT media and training participants who are taught using textbook media. 2) The effect of the interaction between the use of instructional media and linguistic intelligence on English learning outcomes. 3) Differences in English learning outcomes between training participants who are taught using ICT media and those taught using textbook media for training participants who have a high level of linguistic intelligence. 4) Differences in English learning outcomes between training participants who are taught using ICT media and those taught using textbook media for training participants who have a low level of linguistic intelligence. This study used an experimental model with a 2x2 factorial group design. The population in this study were training participants at the Badiklat Language Training Center of the Ministry of Defense Jakarta, the sample was taken using random sampling techniques, so that the sample was 48 training participants, consisting of 24 training participants for the experimental group and 24 training participants for the control group. Retrieval of learning outcomes data using test instruments and linguistic intelligence using a questionnaire. Based on the results of the analysis using descriptive statistics in the experimental class, the average value was 21.90 while the control class had the average value of 20.80. Then the results of the two-way ANOVA test analysis obtained the p-value of the media variable <0.05 (0.022 <0.05). Furthermore, the p-value of media interaction and linguistic intelligence was obtained <0.05 (0.00 <0.05), the Turkey test obtained p-value A1B1-A2B1 <0.05 (0.00 <0.05), and p-value A1B2-A2B2 <0.05 (0.042 <0.05). The results of the study showed 1) The results of learning English for the group of training participants who were taught using ICT media were higher than for the group of participants who were taught using textbook media. 2) There is an interaction between the use of learning media and linguistic intelligence on English learning outcomes. 3) The learning outcomes of the group of training participants who have high linguistic intelligence who are taught using ICT media are higher than the group of training participants who use textbook media. 4) The English learning outcomes of the group of training participants who have low linguistic intelligence who are taught using textbook media are higher than the group of training participants who are taught using ICT media